Let's call x a negative number. We want the product of x and the one next number to it (x + 1) to be 10506. Then, we can write:
![x(x+1)=10506](https://img.qammunity.org/2023/formulas/mathematics/college/pv46rgxmmgqnludhg1vl9ohxggpiazu8xd.png)
Now, we can apply distributive property on the parentheses, and rest 10506 on both sides:
![x^2+x-10506=0](https://img.qammunity.org/2023/formulas/mathematics/college/wlrxuxuye9qk9rl36xcj34b7oo91ry6nh8.png)
And now, we have a quadratic equation in standard form. We can solve this using the quadratic formula:
![\begin{gathered} x_(1,2)=(-1\pm√(1^2-4\cdot1\cdot(-10506)))/(2\cdot1)=(-1\pm√(42025))/(2)=(-1\pm205)/(2) \\ . \\ x_1=(-1+205)/(2)=(204)/(2)=102 \\ . \\ x_2=(-1-205)/(2)=(-206)/(2)=-103 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yivp0q5k8zo5qyebpnh86fv98a2g76sqya.png)
Since we want x to be a negative answer, we take the negative solution, x = -103, And now, we can find the other number:
x + 1 = -103 + 1 = -102
Now, we can verify that the pair of numbers that we have found really are a solution for what we're looking for:
![(-103)(-102)=103\cdot102=10506](https://img.qammunity.org/2023/formulas/mathematics/college/9qpg8qavem5jj4oddi42bl3mg1al0jhcf9.png)
Thus, the equation to solve this is:
![x(x+1)=10506](https://img.qammunity.org/2023/formulas/mathematics/college/pv46rgxmmgqnludhg1vl9ohxggpiazu8xd.png)
And the solution is:
x = -103
x + 1 = -102